Design and application of an electronic model to measure Cost of the University Student using (TDABC) Technique (An applied study on one of the private dental colleges In the Iraqi environment) - Ghazi Maan Faisal; Khawla Hussein Hamdan (Journal of Madenat Alelem University College, 2021)
This research aims to build an electronic model of the technique Time-Driven Activity-Based Costing (TDABC) to help the private dental college study sample to adopt and apply this technique when measuring the cost of a university student. The Financial data was collected for the academic year (2015-2016) for the private dental college as a study sample, and the college name was not mentioned as a result of not agreeing to publish financial data in scientific research, we have employed in the Microsoft Excel program (MS-Excel) for the design and application of the model of (TDABC) technique, Where (MS-Excel) is one of the most used programs on electronic computers by employees who work in the accounting department of most universities and private colleges, which ensures the ease of handling by these departments with this model. The research reached a set of conclusions, the most important of which are: the ease of dealing with the electronic model (TDABC) technique with activities and time driven that are carried out by the resources of universities and private colleges, which explain how important it is to be applied due to the flexibility and speed of updating when any changes occur in the future. The research has reached a set of recommendations, the most important of which are: the necessity of adopting the electronic model for (TDABC) technique by the research sample and working to encourage universities and other private colleges to adopt this model when measuring the cost of a university student.